2001
DOI: 10.1116/1.1380720
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and structural characterization of V2O5/TiO2 catalysts

Abstract: A series of V 2 O 5 /TiO 2 samples was synthesized by sol-gel and impregnation methods with different contents of vanadia. These samples were characterized by x-ray diffraction ͑XRD͒, Raman spectroscopy, x-ray photoelectron spectroscopy ͑XPS͒, and electronic paramagnetic resonance ͑EPR͒. XRD detected rutile as the predominant phase for pure TiO 2 prepared by the sol-gel method. The structure changed to anatase when the vanadia loading was increased. Also, anatase was the predominant phase for samples obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
(51 reference statements)
2
5
0
1
Order By: Relevance
“…This may be related to the higher presence of W O bonds generated by a structure defect due to vanadium incorporation 32, 35 and/or V O bonds associated to polymeric V-O-W chains. 36 In addition, a similar band is reported to correspond to the mode W-O, which is also a bond of tungsten oxide hydrates (WO 3 •nH 2 O), when a water molecule occupies one axial position, 32,37 but our Raman spectra are obtained in dehydration conditions. On the other hand, no changes in the Raman spectra were observed in these catalysts after catalytic tests (Fig.…”
Section: Characterization Of W-v Mixed Oxidessupporting
confidence: 65%
“…This may be related to the higher presence of W O bonds generated by a structure defect due to vanadium incorporation 32, 35 and/or V O bonds associated to polymeric V-O-W chains. 36 In addition, a similar band is reported to correspond to the mode W-O, which is also a bond of tungsten oxide hydrates (WO 3 •nH 2 O), when a water molecule occupies one axial position, 32,37 but our Raman spectra are obtained in dehydration conditions. On the other hand, no changes in the Raman spectra were observed in these catalysts after catalytic tests (Fig.…”
Section: Characterization Of W-v Mixed Oxidessupporting
confidence: 65%
“…The pattern for the Raman spectra is shown in Figure 4, The phases observed by XRD were also confirmed by Raman spectroscopy. In fact, the catalyst shows characteristic peaks at 139 and 282 cm −1 for the orthorhombic vanadium oxide (V 2 O 5 ) [42,43]. For the orthorhombic MoO 3, more intense characteristic peaks are observed at 114, 129, 281, 665, 819 and 997 cm −1 [44,45].…”
Section: Catalyst Characterizationmentioning
confidence: 97%
“…Although Eberhardt et al [97] observed only the presence of V 5+ and V 3+ on the surface after reduction with H 2 or CO, it has often been concluded that the alumina support also stabilizes reduced V 4+ species. The presence of V 4+ species have indeed been measured by many authors for supported vanadium oxides on alumina by Table 6 Results of peak deconvolution of the vanadium photoelectron signal after calcination of a 5 wt.% V/Al 2 O 3 catalyst in air and after reduction with H 2 , CO and CH 4 at 580 • C for 30 min, together with average oxidation states calculated from these fractions [193,196] ESR [87][88][89][90][91][92][93][94][95][96]. As an example, the ESR spectra of the same 5 wt.% V/Al 2 O 3 catalyst after calcination and reduction with CO and H 2 is shown in Fig.…”
Section: Catalyst Activationmentioning
confidence: 99%
“…Electron spin resonance (ESR) is a powerful and quantitative technique to study especially the presence and coordination geometry of the paramagnetic V 4+ (d 1 ) species even under in situ conditions [87][88][89][90][91][92][93][94][95][96]. Vanadium has a nuclear spin of 7 2 , resulting in a complex spectrum with a high number of hyperfine lines.…”
Section: Bm Weckhuysen De Keller / Catalysis Today 78 (2003) 25-46mentioning
confidence: 99%